Ответ:
Пошаговое объяснение:
3x - 4 = 7x + 6
7x - 3x = -4 - 6
4x = -10
x = -10 : 4
x = -2,5
при x = -2,5
==========================
x - 5(x + 3) = 5
x - 5x - 3 = 5
-4x - 3 = 5
-4x = 5 + 3
-4x = 8
x = -8 : 4
x = -2
========================
10(x - 9) = 7
x - 9 = 7:10
x - 9 = 0,7
x = 0,7 + 9
x = 9,7
Copyright © 2025 SCHOLAR.TIPS - All rights reserved.
Answers & Comments
Ответ:
Пошаговое объяснение:
3x - 4 = 7x + 6
7x - 3x = -4 - 6
4x = -10
x = -10 : 4
x = -2,5
при x = -2,5
==========================
x - 5(x + 3) = 5
x - 5x - 3 = 5
-4x - 3 = 5
-4x = 5 + 3
-4x = 8
x = -8 : 4
x = -2
========================
10(x - 9) = 7
x - 9 = 7:10
x - 9 = 0,7
x = 0,7 + 9
x = 9,7
==========================